O papel do Ministério Público do Trabalho na implementação de políticas públicas de combate ao trabalho em condições análogas às de escravo: possibilidades e limites de atuação - Selares, Maurel Mamede (2018)
This paper aims to present a contribution to the study of the work of the Labor Prosecution Office in the implementation of governmental public policies to oppose Labour analogous to slavery. The study starts with a brief approach on the history of slave labor in the world and in Brazil, its conceptualization and beginning of its confrontation in the country. After this, it is proceeded to a conceptualization of public policies, its training cycles and the presentation of public policies to oppose labor analogous to slavery existing in Brazil, emphasizing the role of the Labor Prosecution Office in this process. It is approached not only the importance of the Parquet work, but also some limits to be observed in this desideratum, especially the observance of the existence of budget shortages with the study of the application of reserve of the possible theory; the principle of separation of powers; popular participation in the formulation of public policies; the discretion attributed to the public manager in his actions, the technical limitations of the Public Prosecution Service for the exercise of this duty and the observance of the cycle of formation of public policies in this process. Finally, it is made an analysis on the applicability of limits of the Labor Prosecution Office in the implementation of public policies to oppose labour analogous to slavery in a specific case in the state of Maranhão.